HUBUNGAN PERAN GURU DENGAN MOTIVASI BELAJAR SISWA DI SMA - Delon Tendean; Arie Frits Kawulur; Iwan Kandori (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT This study is motivated by the suboptimal variation in students’ learning motivation, which is presumed to be closely related to the teacher’s role in the learning process. Learning motivation is a crucial factor influencing students’ engagement and academic achievement. This study aims to analyze the relationship and contribution of the teacher’s role to students’ learning motivation at SMA Negeri 1 Motoling Timur. The method employed was a quantitative approach with a descriptive correlational design. The sample consisted of 51 students selected through random sampling. The instrument used was a closed-ended questionnaire that had been validated and proven reliable (α = 0.819 and α = 0.799). Data were analyzed using Pearson correlation and simple linear regression with the assistance of SPSS. The results revealed a positive and significant relationship between the teacher’s role and learning motivation (r = 0.775; p < 0.05), categorized as strong. The teacher’s role contributed 60.1% to students’ learning motivation (R² = 0.601), while the remaining variance was influenced by other factors. These findings highlight the importance of optimizing the teacher’s role as a key factor in enhancing students’ learning motivation in a measurable and sustainable manner. ABSTRAK Penelitian ini dilatarbelakangi oleh variasi motivasi belajar siswa yang belum optimal dan diduga berkaitan langsung dengan peran guru dalam proses pembelajaran. Motivasi belajar merupakan faktor penting yang memengaruhi keterlibatan dan capaian akademik siswa. Penelitian ini bertujuan untuk menganalisis hubungan dan kontribusi peran guru terhadap motivasi belajar siswa di SMA Negeri 1 Motoling Timur. Metode yang digunakan adalah kuantitatif dengan desain korelasional deskriptif. Sampel penelitian berjumlah 51 siswa yang dipilih melalui random sampling. Instrumen berupa kuesioner tertutup yang telah valid dan reliabel (α = 0,819 dan α = 0,799). Data dianalisis menggunakan korelasi Pearson dan regresi linear sederhana berbantuan SPSS. Hasil penelitian menunjukkan bahwa terdapat hubungan positif dan signifikan antara peran guru dan motivasi belajar (r = 0,775; p < 0,05) dengan kategori kuat. Peran guru memberikan kontribusi sebesar 60,1% terhadap motivasi belajar siswa (R² = 0,601), sedangkan sisanya dipengaruhi faktor lain. Temuan ini menegaskan pentingnya optimalisasi peran guru sebagai faktor kunci dalam meningkatkan motivasi belajar siswa secara terukur dan berkelanjutan.